Analisis Kebutuhan Pembelajaran Daring dan Luring Pada Program Studi Pendidikan Guru Sekolah Dasar STKIP Sinar Pancasila - Damian Puling; Augusta De Jesus Magalhaes (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The use of media in every activity is an absolute necessity for an educator because every learning activity that takes place in schools and universities requires educators to utilize technology when they are in the classroom or learning that takes place in a row. This is what happened in the Primary School Teacher education study program at the Sinar Pancasila Teacher Training and Education College (STKIP) where the role of technology is very much needed, both as a medium and as a tool in learning. This research aims to analyze what needs are needed in the Sinar Pancasila Teacher Training and Education College (STKIP) PGSD Study Program as a form of support during the learning process. This research uses a qualitative descriptive method where researchers conduct observations and interviews with students in the study program to find facts about the need for learning media in the PGSD Study Program. This research also aims to analyze the needs of the students of the PGSD Study Program at the Sinar Pancasila Teacher Training and Education College (STKIP) regarding the use of media that have not been met; lack of existing facilities in the study program; and opinions and input from study program students during the learning process as well as solutions offered based on the results of research data.